ITERATIVE LEARNING CONTROL FOR NONLINEAR NONMINIMUM PHASE PLANTS - Hadi (NIM 20104014), Ibnu
ABSTRACT: Learning control is a very effective approach for tracking control in processing occuring repetitively over a fixed interval of time. In this paper an iterative learning control algorithm is proposed for nonlinear nonminimum phase plants. The stable inversion method of Devasia, Chen and Paden is aplied to develop a learning controller for nonlinear nonminimum phase plants. With iterative learning control algorithm we get better controller than previous given controller. Simulation studies demonstrate that perfect tracking of the desired trjectory is achieved for nonlinear nonminimum phase plants.